Resultados psicológicos del entrenamiento físico durante el embarazo. revisión de literatura - Enríquez Reyna, María Cristina; Gallardo Tovar, Olga Liliana; Hernández Cortés, Perla Lizeth; Lagunes Carrasco, José Omar; Carranza García, Luis Enrique
Introduction. In the context of pregnancy or during the postpartum, when a psychological problem occurs, both the mother and the product are affected, hence the actions of the multidisciplinary health team to promote health in this period represent a double wager to improve the quality of dyad life. A literature review was proposed to investigate recent evidence on the utility of planned physical exercise on variables related to psychological health such as mood, anxiety and stress in pregnant women. Methods. A search was made in the Cochrane, Google academic and Pubmed databases. Keywords for the search were: exercise training, pregnant, mood, anxiety, mental health and psychological outcomes. For the analyzes, the description of the type of training, target population, constructs related to mental health and empiric indicators were considered.Results. Twelve articles from nine countries were processed. The quality of the analyzed evidence varies between level II and III of the classification of the National Health and Medical Research Council (1999). Evidence is presented that this type of training has helped to decrease symptoms of depression, to improve mood, physical and mental quality of life. Conclusions. Multiple evidence of different types of training reflect that pregnancy should not be considered as a limitation or inability to participate in any exercise program from the beginning and even until birth.